2006
DOI: 10.1303/aez.2006.63
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic indiscrimination of the grain aphids, Sitobion avenae complex (Hemiptera: Aphididae)

Abstract: Four grain aphids, Sitobion spp. [S. avenae (F.), S. akebiae (Shinji), S. miscanthi (Takahashi) and S. fragariae (Walker)] on various grasses (Poaceae), nominated as Sitobion avenae-complex in this paper, were compared for their morphological and genetic characteristics. For morphological comparison, ten characters frequently used in the identification of S. avenae-complex were compared among samples from various global locations. The results from these comparisons demonstrated that the ranges of specific char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Choe et al . (2006) proposed that the species S. miscanthi and S. akebiae should be synonymised under S. avenae , on the basis of PCA and some molecular data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choe et al . (2006) proposed that the species S. miscanthi and S. akebiae should be synonymised under S. avenae , on the basis of PCA and some molecular data.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative observations suggested some differences in cuticular pigmentation and internal colour between 2n = 18 and 2n = 17 or 20 S. miscanthi , although the difference between the latter two was slight (Turak 1992). Choe et al . (2006) recently concluded, on the basis of morphometric and molecular evidence, that both S. miscanthi and the Asian Sitobion akebiae (Shinji) should be synonymised under Sitobion avenae (Fabricius), the now widespread European grain aphid.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, biological material is usually intercepted at juvenile stages (Choe et al 2006). However, because morphologically based taxonomic keys for preadult material are often unavailable or can be difÞcult to use, reliance on these characters for species identiÞcation is often quite problematic (White and Elson-Harris 1992).…”
Section: Resultsmentioning
confidence: 99%
“…(2005) characterised four new Australian taxa with PCR‐RFLP from the genus Cladopelma Kieffer (Diptera: Chironomidae). In the same way DNA sequence data on the cytochrome oxidase subunit II has revealed that the Sitobion avenae (Fabricius) complex is confirmed by the presence of three closely related taxa with a number of morphological and life cycle variations (Choe et al. 2006)…”
Section: Introductionmentioning
confidence: 85%
“…2004). Molecular markers are particularly useful where morphological and ecological observations are ambiguous (Choe et al. 2006).…”
Section: Introductionmentioning
confidence: 99%